DEVELOPMENT OF CIBUNTU BABAKAN TOFU VILLAGE TOURIST DESTINATIONS BASED ON COMMUNITY EMPOWERMENT THROUGH TOURISM AWARENESS TRAINING AND GUIDING ENGLISH - Astiana, Rachmat; Kemala, Zia (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Babakan Village in Bandung City is known for its tofu industry, particularly Cibuntu Tofu, which has led to the development of a Tourism Village aimed at educating tourists about tofu. The village has begun attracting both local and foreign tourists. However, field observations identified several issues, including the lack of sapta pesona implementation, insufficient guidance, and limited English language skills. To address these challenges, a Community Service program was organized to provide training on tourism awareness, guidance, and basic English skills. This training aimed to enhance the abilities of local resources, particularly Pokdarwis members, who serve as guides, and to encourage the community to embrace sapta pesona as part of the Tourism Aware program. The training used theoretical knowledge transfer and practical simulations, followed by evaluations through quizzes. Fifteen Pokdarwis members, including youth, entrepreneurs, community leaders, and PKK mothers, participated in the program. Post-training surveys indicated that participants found the material both interesting and useful, with many requesting additional training to further enhance their tourism knowledge and skills for the continued development of the tourism village.